Sulforaphane interaction with amyloid beta 1‐40 peptide studied by electrospray ionization mass spectrometry. (30th October 2014) - Nagaveni, V.; Lakshmi, V. V. S.; Prabhakar, S.
<x xml:space="preserve">Abstract</x> RATIONALE Aggregation of amyloid beta 1‐40 (Aβ) in the brain causes Alzheimer's disease (AD) and several small molecules are known to inhibit the aggregation process. Sulforaphane (SFN) is a natural isothiocyanate which is known to prevent various neurodegenerative processes. However, its interaction with Aβ is yet to be explored. Such studies could provide new mechanistic insights for its neuroprotective properties. METHODS Liquid chromatography/electrospray ionization mass spectrometry (LC/ESI‐MS) and in‐source fragmentation experiments were performed on an Orbitrap mass spectrometer. The solution of Aβ and SFN was incubated and analyzed by mass spectrometry. Isotopic distribution patterns, accurate mass values and theoretical product ions were used to analyze the mass spectrometry data. The nature of binding of SFN and its binding sites with Aβ were evaluated by LC/MS and trypsin digestion experiments. RESULTS ESI‐MS analysis of the incubated solution of Aβ and SFN showed a 1:1 complex of [Aβ+SFN]. LC/MS analysis revealed that the solution contains three different [Aβ+SFN] complexes due to covalent binding of SFN to Aβ at three different sites. The in‐source fragmentation experiments revealed that SFN is binding to free NH2 groups (N‐terminal amino acid and lysines) in Aβ. Trypsin digestion experiments further confirmed the SFN binding sites in Aβ. CONCLUSIONS The interaction of SFN, an anticancer agent, with Aβ was studied using ESI‐MS. SFN is found to bind covalently and specifically with the free NH2 group of N‐terminal aspartic acid and the ε‐amino group of lysine at positions 16 and 28. Aggregation assay studies showed a lesser inclination of Aβ to aggregate when SFN is present. Hence the present study helps in understanding the mechanism of the action of SFN on the Aβ peptide. Copyright © 2014 John Wiley & Sons, Ltd.